The chemical and microbiological assessment of water and soil samples. Report number 1 - Cesoniene, Laima; Dulova, Niina; Eymontt, Andrzej; Gugalai, Magdalena; Joutsjoki, Vesa; Pachel, Karin; Räsänen, Kati; Virtanen, Yrjö; Urtãne, Loreta (My University, 2017)
The aim of this work was to make an enviro-hygienic (chemical and microbiological) assess-ment for the waste water treatment systems In the VillageWaters-project partner countries. There are different pilots where the technological changes will be conducted during the project. There are two in two in Estonia (Kolgaküla and Valkla), two in Finland (Gennarby and Nurmijärvi), two in Latvia (Svētciems and Ainaži), one Lithuania (Leitgiriai) and two in Poland (Krynica-Zdrój and Sokoly). The pollution of untreated wastewater flowing into the Gennarby, Finland wastewater treatment plant has been assessed by identifying the BOD7, pH value and concentrations of suspended materials, phosphorus and nitrogen. Accordingly, the present purification rates seem to meet reasonably the requirements set for the small communities of the scattered dwellings. Removal of organic matter (BOD ) exceeds the requirement. Reduction of total nitrogen is slightly below the required level. Reduction of total phosphorus is significantly lower than the requirement. The second pilot plant is located in southern Finland, Nurmijärvi. The results show that treatment of the sewage yields to almost 97% reduction in total phosphorus and nearly 79% reduction in total nitrogen. This indicates the efficiency of soil filtration system in the removal of nutrients and reduction of eutrophic waste reduction in natural waters. The pollution of untreated wastewater flowing into the Leitgiriai, Lithuania wastewater treatment plant has been assessed by identifying the BOD7, pH value and concentrations of suspended materials, phosphorus and nitrogen. The results have shown that during the treatment process the wastewater is treated inefficiently and vary: submerged materials 29–47%, biochemical oxygen consumption in 7 days (BOD7 ) - 88 -95%, it means that the BDS7 value in the released wastewater is higher than that in the inflowing wastewater; total nitrogen (Nt) –4 - 46%, total phosphorus (Pt) 2- 86 %. During the assessment it was found that the treatment of total nitrogen and ammonium nitrogen has changed the most (%). It was found that the values of nitrate nitrogen, total nitrogen, electrical conductivity were statistically significantly higher 500 m after the wastewater discharger than 100 m before the wastewater discharger. The differences between the ammonium nitrogen and total phosphorus concentrations were not significant. The pollution of untreated wastewater flowing into the Idźki-Wykno village, Sokoly, Poland wastewater treatment plant has been assessed by identifying the BOD7, pH value and concentrations of suspended materials, phosphorus and nitrogen. The suspended solids have been reduced by nearly 90%, the BOD5 has been reduced by nearly 86% and the amount of wastewater was less than 5 m3/day, so all condition contained in the Polish “Regulation of the Minister of the Environment from 18 November 2014 on the conditions to be met for the discharge of sewage into water or soil and on substances particularly harmful for the water environment " have been met. The results have shown that during the treatment process the wastewater is treated efficiently. The efficiency of natural individual domestic wastewater treatment plant in Idźki-Wykno village in Poland is similar to efficiency of wastewater treatment plant in Gennarby in Finland.. The second pilot domestic wastewater treatment plants are located in the village of Słotwiny in the municipality of Krynica-Zdrój It is a mountain region in the south of Poland. Comparing the quality of untreated wastewater coming from household in Sokoły municipality and Krynica-Zdrój municipality you can notice that wastewater coming from household in Krynica-Zdrój is less polluted then wastewater coming from Sokoły municipality. Certainly, it depends on many factors. The wastewater is treated sufficiently ac-cording to BOD5 and suspended solids. The requirements contained in Regulation of the Minister of the Environment from 18 November 2014 are fulfilled.
Raportti ilmestynyt Interreg Baltic Sea Region rahoittamassa hankkeessa VillageWaters
Keywords: purification technologies; Enviro-hygienic assessment (EHA); microbes; wastewater treatment; nutrients; microorganisms